Regra-matriz da Cofins incidente sobre a receita bruta - Sehn, Solon (2005)
From a conception which differentiates norm, enunciation and proposition, the present study had for object the construction of Cofins s standard rule applicable to the gross revenue in the Brazilian law. The study carried through a provisory cross-section into the rule s binary completeness, concentrating only in the criteria used to recognize the event described in the antecedent-proposition and the legal relation provided by the consequence-proposition. From the Federal Law n.° 10,833/2003, interpreted according to the Constitution (art. 195, I, a ), the study concluded that the tax presents as material hypothesis s criteria the behavior of to gain (verb) gross revenue (complement). The space criteria coincides with the territorial ambit of the law validity (any place of the domestic territory), while the time criteria is the following day of the base period, when it becomes possible determine the total revenue s value. The legislation, on the other hand, defines the Federal Union as active subject and all the companies, as passive subject (taxpayer). The standard aliquot is 7,6% of the taxable income, that, in turn, corresponds to all gross revenue gained in the month. Those exceptions provided by the Federal Law n.° 10,833/2003 (art. 1.°, § 3.°) do not exhaust all the possibilities.